2011
DOI: 10.1148/radiol.11110686
|View full text |Cite
|
Sign up to set email alerts
|

Gliomas: Histogram Analysis of Apparent Diffusion Coefficient Maps with Standard- or High-b-Value Diffusion-weighted MR Imaging—Correlation with Tumor Grade

Abstract: Histogram analysis of ADC maps based on entire tumor volume can be a useful tool for grading gliomas. The fifth percentile of the cumulative ADC histogram obtained at a high b value was the most promising parameter for differentiating high- from low-grade gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
252
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 305 publications
(272 citation statements)
references
References 30 publications
15
252
2
3
Order By: Relevance
“…7,23 Studies that reported central necrotic regions for either tumor grade were excluded. Some studies separated tumor core values for enhancing and nonenhancing components, and these were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…7,23 Studies that reported central necrotic regions for either tumor grade were excluded. Some studies separated tumor core values for enhancing and nonenhancing components, and these were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Glioma grading using conventional MRI sequences remains challenging and numerous studies aimed at determining the utility of MRS (19) or diffusion imaging with apparent diffusion coefficient (ADC) maps computation (1,12,15,22,29) in this setting.…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…[25][26][27] In addition, a histogram-based approach with ADC maps has been used in neuro-oncologic imaging to differentiate tumor progression from pseudoprogession and to evaluate tumor grades and even gene mutations. 25,[28][29][30] Histogram analysis is considered to represent tumor heterogeneity, which is well known to affect tumor response to chemoradiation therapy. Therefore, analysis of the spatial heterogeneity of the tumor cellularity by histogram analysis of ADC maps could help evaluate and predict tumor response to treatment.…”
Section: Introductionmentioning
confidence: 99%